Sensitivity to change and clinical correlations of the novel DACtylitis glObal Sonographic (DACTOS) score in psoriatic arthritis. (28th December 2020) - Girolimetto, Nicolò; Zabotti, Alen; Tinazzi, Ilaria; Possemato, Niccolò; Costa, Luisa; Batticciotto, Alberto; Canzoni, Marco; Citriniti, Giorgia; Lucia, Orazio De; Figus, Fabiana; Idolazzi, Luca; McConnel, Rebecca; et al.
Abstract: Objective: The aim of the study is to assess the performance of the DACTOS (DACtylitis glObal Sonographic) score in a PsA dactylitis clinical setting. In particular, we evaluated the ability of DACTOS to identify the affected fingers, its sensitivity to change after treatment, the correlations between DACTOS and clinical parameters, and the capacity of the score to identify the treatment responders. Methods: Forty-six consecutive patients with symptomatic PsA hand dactylitis were enrolled. A total of seventy-three dactylitic digits were evaluated clinically and sonographically before and after treatment in this observational and prospective study. Clinical assessment included the Leeds Dactylitis Index-basic (LDI-b) score and visual analogue scales for pain (VAS-p) and functional impairment (VAS - FI). Sonographic lesions were investigated using high-frequency ultrasound with grey scale and power Doppler features according to the DACTOS score. Correlations between the DACTOS score and the clinical parameters were assessed at baseline, 1 month (T1) and 3 months (T3). Results: We observed significant improvements in all of the assessed clinical parameters and the DACTOS scores after dactylitis treatment. There was a statistically significant correlation between the variation of all clinical parameters (VAS-p, VAS-FI and LDI-b) and the DACTOS score at T1 and T3 evaluations. We found statistically significant differences in the DACTOS score between clinical responder and non-responder groups ( P < 0.001) and between clinical remission and non-remission groups ( P < 0.001). Conclusion: The DACTOS score performs well in real-life clinical settings in terms of sensitivity to change and correlations with clinical features in PsA dactylitis.